2015
DOI: 10.1007/s00213-015-4134-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of methamphetamine-mediated behavioral sensitization by overexpression of Mu opioid receptors in nucleus accumbens and ventral tegmental area

Abstract: Our data suggest a differential modulation of Meth sensitization by overexpression of MOR in NAc and VTA. Regional manipulation of MOR expression through AAV may be a novel approach to control Meth abuse and psychomimetic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Meth sensitization was induced in mice after repeated administration of Meth ( n = 16, sensitizing dose, 2.5 mg/kg/day, s.c.) for 7 days (days 0 to 6, see timeline, Fig. 1A ) 34 . Control noS animals received a daily saline injection ( n = 22, s.c., × 7 days).…”
Section: Resultsmentioning
confidence: 99%
“…Meth sensitization was induced in mice after repeated administration of Meth ( n = 16, sensitizing dose, 2.5 mg/kg/day, s.c.) for 7 days (days 0 to 6, see timeline, Fig. 1A ) 34 . Control noS animals received a daily saline injection ( n = 22, s.c., × 7 days).…”
Section: Resultsmentioning
confidence: 99%
“…Crossing the central squares by METH-treated mice more than the control group implied that had an anxiety-like behavior. It has been reported that METH-induced behavioral sensitization occurs after repeated administration in rodents ( 17 ). In line with our results, Struntz and Siegel reported increased locomotor activity and anxiety-like behavior in adult mice that were treated with a single low dose METH, 4 mg/kg ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shen found that repeated METH administration initiated behavioral sensitization in wild-type mice, and these changes were attenuated in μ-opioid knockout mice, suggesting that MORs regulate behavioral sensitization of METH Shen et al (2010), which is consistent with Kuo's findings that the role of the u-opioid receptor is associated with its location in the brain. Using a stereotactic injection technique, AAV-MORs was injected into the NAc or the ventral tegmental area (VTA) of adult mice and MORs overexpression in NAc and VTA differentially affected METH sensitization, with MORs in VTA enhancing behavioral sensitization while MORs in the NAc region had an antagonistic effect (Kuo et al, 2016). Mounting evidence suggests that neuroplasticity changes are related to behavioral sensitization.…”
Section: Behavioral Sensitization and Cross-sensitizationmentioning
confidence: 99%